American't Breathe - Panayides, Angelos (My University, 2023)
There was a theme to this year's International Graphic Design Festival Plaster: photographic material as the subject matter of graphic design in the form of a collage or as the core of the composition. Photography has enormous creative potential which has been largely neglected by designers in recent years.
Keywords: International; Graphic design; Festival